f(R, T) models applied to baryogenesis - Baffou, E.H.; Houndjo, M.J.S; Kanfon, D.A.; Salako, I.G. (Springer Link, 2019)
This paper is devoted to the reproduction of the gravitational baryogenesis epoch in the context of f (R, T ) theory of gravity, where R and T are respectively the curvature scalar and the trace of the energy-momentum tensor, respectively. It is assumed a minimal coupling between matter and gravity. In particular we consider the following two models, f (R, T ) = R + αT + βT 2 and f (R, T ) = R + μR2 + λT , with the assumption that the universe is filled by dark energy and perfect fluid where the baryon to entropy ratio during a radiation domination era is non-zero. We constrain the models with the cosmological gravitational baryogenesis scenario, highlighting the appropriate values of model’s parameters compatible with the observation data of the baryon-entropy ratio.
Since antiparticles were first predicted and observed [1], it has been clear that there exist high degree of matter antimatter symmetry. This observation is a stark contradiction to the phenomena of everyday and cosmological evidence, particularly the fact that our universe consists of almost entirely matter with little primordial antimatter.
Keywords: gravitational baryogenesis; energy-momentum; antiparticles; antimatter